2018
DOI: 10.4236/ajps.2018.913202
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficient Analyses of Cowpea (<i>Vigna unguiculata</i> L.) Landraces in Ethiopia

Abstract: Understanding the nature and extent of association between yield and yield related traits is the prerequisite study for any underutilized crop improvements of sustainable genetic enhancement. However, there is a lack of sufficient information on seed yield and related trait correlation and path coefficient analysis of cowpea in Ethiopia. To fill the existing knowledge gap, the present study was conducted to determine the nature and extent of phenotypic and genotypic correlation and path coefficient analysis am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…Significant and positive phenotypic correlation of seed yield was perceived with harvest index (0.838**), number of pods per plant (0.710**), number of seeds per pod (0.415**), plant height (0.302**) and protein content (0.218*) hinting that these attributes are the primary yield determinant in cowpea. These findings were in accordance with the results of Srinivas et al (2017) [20] ; Tsegaye et al (2018) [24] and Walle et al (2018) [26] . The phenotypic correlation coefficient of pod length (-0.212*), days to 50 per cent flowering (-0.328**) and days to maturity (-0.259*) was recorded significantly negative with seed yield per plant.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Significant and positive phenotypic correlation of seed yield was perceived with harvest index (0.838**), number of pods per plant (0.710**), number of seeds per pod (0.415**), plant height (0.302**) and protein content (0.218*) hinting that these attributes are the primary yield determinant in cowpea. These findings were in accordance with the results of Srinivas et al (2017) [20] ; Tsegaye et al (2018) [24] and Walle et al (2018) [26] . The phenotypic correlation coefficient of pod length (-0.212*), days to 50 per cent flowering (-0.328**) and days to maturity (-0.259*) was recorded significantly negative with seed yield per plant.…”
Section: Resultssupporting
confidence: 93%
“…Significant and positive correlation was registered by harvest index with number of pods per plant (0.394**) and number of seeds per pod (0.310**). Similar findings were reported by Walle et al (2018) [26] . At phenotypic level, the positive direct effect on seed yield per plant was majorly by harvest index (0.9094), biological yield per plant (0.3906), number of pods per plant (0.2089), plant height (0.0604), 100-seed weight (0.0080), number of branches per plant (0.0058), number of seeds per pod (0.0047), protein content (0.0023) and pod length (0.0003) indicating the direct selection for these traits in order to improve seed yield of cowpea whereas, highest negative direct effect were reported for days to 50 per cent flowering (-0.0204) and days to maturity (-0.0094).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results indicated that straw yield (1.068) had highest positive direct effect on seed yield followed by harvest index (0.741). Similar observations of high direct effect of harvest index and pods per plant on seed yield was observed by Walle et al (2018) in their study on assessing the correlation and path coefficient in cowpea landraces from Ethiopia. However positive direct effect of straw yield on grain yield in the current study was contrary to some reports (Peksen and Artik, 2004) which had a nonsignificant negative effect on grain yield.…”
Section: Path Coefficient Analysissupporting
confidence: 85%